Unpacking Technical Vocabulary Barriers in IoT Assembly: A Qualitative Needs Analysis of Vocational Students - Sultan, Arifudin; Agustina, Yulia; Maysuroh, Siti; Usuluddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid integration of digital technologies in vocational education demands highly specialized linguistic competencies, particularly for engineering students navigating complex instructional manuals and software interfaces. This qualitative study explores the specific English language barriers encountered by vocational learners and investigates their target needs for instructional media development. Framed within the English for Specific Purposes paradigm, the research involved 31 students in the 11th grade of the Industrial Electronics Engineering program at SMK Negeri 3 Selong, Indonesia. Data were gathered through open ended needs analysis questionnaires and subsequently processed using an interactive qualitative analysis model encompassing data condensation, data display, and conclusion drawing. The findings reveal a multifaceted language barrier where students simultaneously struggle with digital software interfaces, printed instructional manuals, and the physical identification of hardware components. Furthermore, the analysis indicates a strong student demand for a highly contextualized, multimodal learning approach. The participants explicitly requested instructional videos that synchronize authentic visual demonstrations of Internet of Things module assembly with clear bilingual text overlays to mitigate cognitive overload. This study concludes that general English instruction is fundamentally inadequate for vocational contexts, emphasizing the urgent necessity for tailored multimedia interventions to enhance technical vocabulary mastery.